Survey on how Australian rheumatologists use musculoskeletal ultrasound (MSUS), including challenges and unmet needs - Zoe Brown; Fredrick Joshua; Helen Keen; Anita Lee (WFUMB Ultrasound Open, 2023)
Objective: Worldwide there is increasing use of musculoskeletal ultrasound (MSUS) in clinical practice, particularly by rheumatologists. Despite reported high levels of interest in the use of MSUS, lack of education and experience are often reported as barriers to rheumatologists performing MSUS in clinical practice. To evaluate current MSUS practices in Australia, we undertook a survey of rheumatologists who are current members of an Australian MSUS special interest group. Methods: Descriptive and summary statistics of responses to a web-based survey to rheumatologists who had attended a workshop with the Australian Musculoskeletal Imaging Special Interest Group (AMISIG) were undertaken. Results: Of thirty-six respondents, 97.2 % reported using MSUS as part of clinical care, and more than a quarter also use MSUS for research and teaching. The most frequent indication for MSUS use in 94.4 % of clinicians was for early diagnosis of rheumatic diseases, followed by monitoring response to treatment. Barriers to use of MSUS were identified, including time constraints, costs and lack of training post courses and experience. To support MSUS use in Australia, respondents nominated more “hands-on” supervised training courses and supervision of advanced trainees. Conclusion: MSUS use by surveyed Australian rheumatologists is most frequently to make an early diagnosis of rheumatic diseases as well as in monitoring response to treatments, in research and in teaching activities. Australian clinicians identified that increased clinical education in MSUS, particularly for rheumatology trainees, was needed.